Analisis Pendekatan Feminisme Pada Lagu Melly Goeslaw "Mengapa Bila Aku Perempuan" - Anita Sari (Alinea: Jurnal Bahasa, Sastra dan Pengajaran, 2024)
This study analyzes the feminist approach in Melly Goeslaw's song “Mengapa Bila Aku Perempuan.” Music is often used as a medium to voice gender issues, women's experiences, and critiques of social norms. This research employs textual analysis with a feminist approach to interpret the lyrics' meanings. The results reveal that Melly Goeslaw's song emphasizes women's liberation from gender discrimination and stereotypes, highlighting the importance of challenging societal norms and asserting autonomy. The song portrays women as strong, independent individuals who deserve recognition and equality. Thus, this work serves not only as entertainment but also as an educational tool that upholds feminist values.